ETR300 Shaky DeNata Cafe / Siti Shuhadah Mohamad... [et al.] - Mohamad, Siti Shuhadah; Abd. Rahaman, Nur Illiana; Beti, Ignatius Nyalayang; Abdullah, Ainul Nadia (2011)
The name of our company is Shaky DeNata Café. The business is in form of enterprise which consists of four members. Each partner contributes certain amount of capital as agreed in agreement. The main business activity we make and serving the foods and drinks by our own. Coconut Shake is our privilege. Concept of our business IS like a mini bar restaurant concept. Our business operation is at 10 am to 10 pm on weekdays and on weekends and public holiday at 10 am to 1 1 pm. Our shop will close on Monday every week for staff rest. There are no sleeping partners and all are entitled to participate in the business management. We agree that Siti Shuhadah binti Mohamad as the General Manager and Administration Manager, Ignatius Nyalang ak Beti as the Operational Manager, Nur Illiana Inti Abd Rahaman as Marketing Manage and Ain Nadia binti Abdull as the Financial Manager. The selection of General Manager is based on consensus among all the partners and selected based on the experience, skill and ability.